Prawa człowieka i obywatela w Konstytucji RP a przyzwolenie na obecność islamu w Polsce - Maja Biernacka (Ksiegarnia Akademicka Publishing, 2018)
Human and Civil Rights in the Constitution of the Republic of Poland and Approval of the Presence of Islam in Poland. Studies of Students’ Attitudes in the City of Bialystok The article is dedicated to the confrontation of the constitutional grounds of the religious liberties in Poland and institutional enshrinement of faith with social attitudes towards Muslims, exemplified by the data obtained from a study conducted by a team from the University of Białystok: Maja Biernacka (head), Wojciech Wądołowski and Łukasz Wołyniec in the year 2015. The research is dedicated to a large spectrum of issues, including attitudes towards Muslims as displayed by students of three major public academic institutions in Białystok, i.e. University of Białystok, Medical University of Białystok and Białystok University of Technology. The data was collected via a standardized questionnaire, allowing for the answers to be systematically compared and contrasted. The module of the research which is presented in this article refers to contextualized scenarios related to respondents’ approval of the expression of the creed and everyday practices which are grounded in Islamic tradition.